2018
DOI: 10.1002/nau.23556
|View full text |Cite
|
Sign up to set email alerts
|

De novo overactive bladder after robot‐assisted laparoscopic radical prostatectomy

Abstract: The incidence rate of de novo OAB after RARP was about 40%, and seemed unexpectedly high. Decreased urethral function was significantly related to de novo OAB after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…Actually, some studies have reported the presence of postoperative DO after RP. 20,21 The postoperative BOO index in the DU group was also significantly decreased compared with the non-DU group. The BOO index is defined as PdetQmax minus two times Qmax.…”
Section: Discussionmentioning
confidence: 85%
“…Actually, some studies have reported the presence of postoperative DO after RP. 20,21 The postoperative BOO index in the DU group was also significantly decreased compared with the non-DU group. The BOO index is defined as PdetQmax minus two times Qmax.…”
Section: Discussionmentioning
confidence: 85%
“…UPP were measured twice at each time, and the average maximum urethral closing pressure (MUCP) was obtained. RARP was carried out via the transperitoneal approach with six ports using the da Vinci S system (Intuitive Surgical) as previously reported 7 …”
Section: Methodsmentioning
confidence: 99%
“…RARP was carried out via the transperitoneal approach with six ports using the da Vinci S system (Intuitive Surgical) as previously reported. 7 To evaluate predictive factors for low preoperative urethral function, we analyzed the association between preoperative MUCP and the following factors: age, body mass index, American Society of Anaesthesiologists physical status, history of diabetes mellitus and hypertension, prostate volume, international prostate symptom score (IPSS), erectile function domain scores using the International Index of Erectile Function 15 (IIEF15) (question 1 + 2 + 3 + 4 + 5 + 15), and current medication use, such as calcium channel blockers, α-adrenoceptor blockers, angiotensin receptor blockers, and angiotensin-converting enzyme inhibitors. Prostate volume was measured using abdominal ultrasound.…”
Section: Study Amentioning
confidence: 99%
“…In a recent study, Mastukawa et al identified that low maximum urethral closure pressure at baseline and its decrease postoperatively were strong predictors of de novo post-rPR OAB underlying the role of the intrinsic sphincter deficiency on the pathophysiology of OAB (40).…”
Section: Oab and Urgency Incontinencementioning
confidence: 99%